Policy: EU data protection regulation-harming cancer research - Kerr, D (Nature Publishing Group, 2014)
The cancer community is deeply concerned about the unintended consequences of the current wording of the European Union (EU) draft Regulation on Data Protection, which may challenge the survival of retrospective clinical research, biobanking, and population-based cancer registries in the EU. This directive could negatively affect Europe's competitiveness in cancer research.